¿La diabetes mellitus tipo 2 se corrige mediante cirugía bariátrica? Breve revisión de la literatura. - Gosch C., Marianne; Rojas M., Pamela (Revista Hospital Clínico Universidad de Chile, 2013)
Type 2 diabetes mellitus (T2D) is a health problem worldwide, and is associated with serious health consequences. The development of T2D has a strong association with obesity, sedentary lifestyle, genetic factors and other associations of diabetes. Faced with this problem, bariatric surgery has evolved as the treatment that produced a greater decrease in body weight in the long term, unlike the medical treatment. Moreover, it is postulated that bariatric surgery currently may have a beneficial effect in improving the treatment or even diabetes remission in obese patients.